Pemasaran Seni Lukisan Doodle Kajian Ke Atas Claudia Anne Allin - Nur Ashiekin, Binti Zam Mohammad Kinal. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This research is about the marketing art doodle painting on Ms. Claudia Anne Allin in Kuching. Sarawak. This research focuses on the marketing methods used by Ms. Claudia Anne Allin to market her doodle drawings and the best way to market the doodle drawings. The study was conducted l,sing qualitative methods by interviewing the relevant informants. 'it is hoped that the findings will help Ms. Claudia Anne Allin to market her artwork.